How do you multiply #(3x^2 + 2x + 4)(2x + 1)#?

2 Answers
Apr 24, 2018

Answer:

#6x^3+7x^2+ 10x +4 #

Explanation:

You have to take each number in the first bracket and multiply it by the second one.
First lets do #3x^2#
#(3x^2)*(2x)# and (3x^2)*1# This will give #6x^3# and #3x^2#

Then #2x#
#2x * 2x# and #2x *1#
This will give #4x^2# and #2x#

Then #4#
#4*2x# and #4*1#
This will give #8x# and #4#

Taking all these, you simply just add them together!

Apr 24, 2018

Answer:

#= 6x^3 + 7x^2+10x+4#

Explanation:

Do the first term in the first bracket multiplied by the first term in the second bracket. Do the same with the first term in the first bracket (#3x^2#) and the second term of the second bracket.

(#3x^2#)x(#2x#) = #6x^3#
(#3x^2#)x(#1#) = #3x^2#

[For powers, use the rule:

#a^m#x#a^n# = #a^m+n# (where #x# is actually #x^1# from example above which simply calculates to #x#)

Then multiply any real numbers as you normally would (#3#x#2#)]

For the next step, multiply the second term of the first bracket to the first of the second bracket:

(#2x#)x(#2x#) = #4x^2#
(#2x#)x(#1#) = #2x#

Proceed to the final term in the first bracket and follow the same steps:

(#4#)x(#2x#) = #8x#
(#4#)x(#1#) = #4#

Simplify by adding all like terms together:

#= 6x^3 +3x^2+4x^2+2x+8x+4#
#= 6x^3 + 7x^2+10x+4#

www.dr-aart.nl